Correlation Analysis Between Losses with Boiler Opacity and Ambient Air Quality Effect on Capacity of Pulmonary Function of Palm Oil Mill Employees (Comparative Study on PT. AIP and PT. BNS) - Rinno Ferryno; Aras Mulyadi; Nursyirwani Nursyirwani (Jurnal Ilmu Lingkungan, 2017)
The comparative research was conducted from October 2016 until January 2017 at two companies namely PT. AIP Teluk Siak Factory (TSF) and PT. BNS Mandah Factory (MDF) in Riau Province. The purposes of the research were to analyze the correlation between oil and palm kernel (losses) that is entrained fuel (fibers and shells) with opacity emissions boiler in TSF and MDF, and to analyze the impact of ambient air SO2 levels on capacity pulmonary function palm oil mill employees (TSF and MDF) with controll variables personel protective aquipment, age, smoking habits, and tenure.Based on the results, The correlation strength of oil loss in fiber cyclone, kernel loss in fiber cyclone, and kernel loss in winowing with boiler opacity in TSF and MDF is low correlation (R value of 0.320). The simultaneous and partial oil loss in fiber cyclone, kernel loss in fiber cyclone, and kernel loss in winowing were not significantly affect the boiler opacity in both factories (F test and t test of significance  > 0.05). R2 value of 10.2% indicates the magnitude of losses effect on opacity. This analysis explains that the losses are not the dominant factor affecting the boiler opacity. The boiler opacity is influenced by quality and balance fuel with oxygen, continuity process in mill and optimization of boiler performance as the operation practice, maintenance and boiler sparepart replacement. The impact of ambient air SO2 levels on capacity pulmonary function when controlled by age and tenure showed significant values (p < 0.05). Age and tenure are factors that differentiate magnitude of the impact of ambient air SO2levels on capacity pulmonary function. While the impact of ambient air SO2 levels on capacity pulmonary function when controlled by personel protective aquipment (PPE) and smoking habits did not show significant values (p > 0.05) in both factories. PPE and smoking habits are not factors that differentiate magnitude of the impact of ambient air SO2 levels on capacity pulmonary function.